Digital Supply Chain Management: A Study on Bangladeshi Fashion and Accessories Industry’s E-retailers. (Global Journal of Management and Business Research, 2024)
This study aims to examine the challenges faced by e-retailers in the Bangladeshi fashion and accessories industry s supply chain and explore the potential benefits of integrating digital supply chain management systems The study addresses the gap in understanding the obstacles hindering the growth of e-commerce within the fashion and accessories sector in Bangladesh and the potential solutions to improve supply chain efficiency Qualitative research methods were employed involving interviews with 55 e-retailers and thematic analysis to assess the data The research reveals sourcing challenges and lengthy lead times as significant barriers in the industry It also highlights the positive impact of digital supply chain systems on delivery efficiency with a low adoption rate among e-retailers The findings suggest that by implementing integrated information-sharing systems within the supply chain could revolutionize the e-commerce fashion and accessories industry in Bangladesh improving responsiveness and reducing lead times
Keywords: digital supply chain management; bangladesh e-commerce growth; supply chain efficiency; information sharing system; fashion and accessories sourcing